2011
DOI: 10.3354/ab00347
|View full text |Cite
|
Sign up to set email alerts
|

Meiobenthic community underneath the carcass of a stingray: a snapshot after natural death

Abstract: The impact of large food falls and carrion on meiobenthic communities remains little understood. The objective of the present study was to investigate whether the carcass of a stingray, encountered fortuitously in an Australian estuary, affects the underlying meiobenthic community, in particular nematode assemblages. The integrity of the skeleton and the low redox values observed under the carcass suggest that the cadaver had been slowly and chiefly decomposed by microbes. The abundance and number of meiofauna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Whereas at the local scale C. taxifolia have reduced species richness at 1 of the sites, at the larger scale it caused an apparent increase in species richness by favouring species that were seemingly absent from the native environments. As suggested by previous studies (Gallucci et al 2008, Fonseca et al 2011b) these species are probably rare in the surrounding environments (particularly in the superficial layers, i.e. 0 to 2 cm) and take advantage of the 'unfavourable' conditions created by C. taxifolia and the consequent lack of competition to prosper.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas at the local scale C. taxifolia have reduced species richness at 1 of the sites, at the larger scale it caused an apparent increase in species richness by favouring species that were seemingly absent from the native environments. As suggested by previous studies (Gallucci et al 2008, Fonseca et al 2011b) these species are probably rare in the surrounding environments (particularly in the superficial layers, i.e. 0 to 2 cm) and take advantage of the 'unfavourable' conditions created by C. taxifolia and the consequent lack of competition to prosper.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies from shallow-water habitats have shown that nematode communities associated with decaying fauna are distinct from communities in nearby areas (e.g., Gerlach 1977, Ó lafsson et al 1992, Fonseca et al 2011). Several studies from shallow-water habitats have shown that nematode communities associated with decaying fauna are distinct from communities in nearby areas (e.g., Gerlach 1977, Ó lafsson et al 1992, Fonseca et al 2011).…”
Section: Disturbancementioning
confidence: 99%
“…Similarly, the abundance and diversity of meiofauna under an estuarine stingray carcass were significantly lower when compared with samples away from the carcass (Fonseca et al 2011). Only a few nematode species, typical of hypoxic/anoxic sediments, were more abundant under this carcass (Fonseca et al 2011).…”
Section: Meiofauna From Carcasses and Sunken Woodsmentioning
confidence: 99%
“…Similarly, the abundance and diversity of meiofauna under an estuarine stingray carcass were significantly lower when compared with samples away from the carcass (Fonseca et al 2011). Only a few nematode species, typical of hypoxic/anoxic sediments, were more abundant under this carcass (Fonseca et al 2011). Among copepods associated with sunken wood, Xylora bathyalis is also found living in hydrothermal vents and cold seeps (Hicks 1988;Cuvelier et al 2014;Plum et al 2015).…”
Section: Meiofauna From Carcasses and Sunken Woodsmentioning
confidence: 99%